Non-Carcass Composition of Thin Tail Sheep Fed Indigofera Zollingeriana with Different Maintenance System - A. R. Jatnika; I. Munandar; Husni; S. Nealma; R. Priyanto; L. Abdullah (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
The composition of non-carcass thin-tailed sheep fed Indigefera zollingeriana with different rearing systems, was evaluated using twenty sheep with an average initial body weight of 18.3 ± 2.01 kg. The variables observed in this study included the weight of the head, feet, skin, tail, liver, spleen, lungs, heart, kidneys, rumen, reticulum, omasum, abomasum, intestines, empty viscera and omnetal fat. The design used in this study was a factorial completely randomized design (CRD) with five replications. Feed is treatment factor one (P1 = grass + commercial concentrate and P2 = grass + Indigefera zollingeriana) and maintenance is treatment factor two (SI = Semi Intensive and I = Intensive). The results of the study were analyzed by analysis of covariance. and the correction factor is the initial weight of the sheep. The results of this study showed that giving P2 to sheep resulted in lower tail weight but higher kidney weight (P<0.05). In addition, there was an interaction effect (P< 0.05) between treatments on the weight of theomasum and abomasum, where the sheep with P1I treatment had the highest omasum and abomasum weights, while the lowest omasum and abomasum weights were in the P2I treatment.